Adsorptive desulfurization of diesel oil using nickel nanoparticle-doped activated carbon beads with/without carbon nanofibers: Effects of adsorbate size and adsorbent texture. (1st February 2017) - Prajapati, Yogendra Nath; Verma, Nishith
Graphical abstract: Highlights: Efficient Ni-doped CNF-containing adsorbents were prepared for ADS of diesel oil. The adsorbate size and adsorbent textures influenced the adsorption capacity. Ni-CNF/ACBs showed higher adsorption capacity than Ni/ACBs in a commercial oil. Abstract: Nickel (Ni)-doped activated carbon beads (ACBs) with/without carbon nanofibers (CNFs) were synthesized for the efficient desulfurization of diesel oil by adsorption. The materials were characterized for their physico-chemical properties, using the BET, SEM, XRD, and TPD analysis. The in-situ dispersed Ni nanoparticles in the ACBs served the dual role of catalyzing the growth of the CNFs (average thickness c.a. 70 nm) across the ACB surface and the removal of S-containing compounds from the liquids. The adsorption capacity of Ni/ACBs (without CNF-containing adsorbents) was approximately 3.5 times higher than that of Ni-CNF/ACBs for the large sized dibenzothiophene molecules, because of the higher BET surface area and pore volume of the former adsorbent. On the contrary, the adsorption capacity of Ni-CNF/ACBs was higher than that of Ni/ACBs for the small sized thiophene molecules, despite the BET surface area and pore volume being smaller in the CNF-containing adsorbent, indicating that the π-complexion interactions were dominant over physisorption in the graphitic CNFs. The comparative adsorption data indicate that the adsorption capacities of the prepared Ni-containing adsorbents with/without CNFs in this study were greater than most of the adsorbents discussed in the literature. This study assumes significance from the perspective of selecting suitable adsorbents for the different sized-S-compounds in diesel oil.